California wildfires and planetary health - Pey, Peili (2025)
The California wildfires are an environmental disaster, but they also point to a deeper set of challenges, not only for the United States of America but for the global community. Such wildfires, which are ever-increasing in frequency and scale due to the impact of climate change, result in structural damage and long-term health risks that disproportionately affect vulnerable communities and are a costly burden to the state. A planetary health approach highlights the need for a more comprehensive understanding of the climate-environment-health interface in managing the risk and incidence of wildfires.